2009
DOI: 10.1177/0040517509342316
|View full text |Cite
|
Sign up to set email alerts
|

Nano-cotton Fabrics with High Ultraviolet Protection

Abstract: Ultraviolet resistant cotton fabrics were developed by coating with ZnO and TiO2 nanoparticles. The ZnO nanoparticles applied on cotton yarns were found to withstand the knitting operation. Meanwhile, the TiO 2 nanoparticles applied on the bleached as well as reactive dyed cotton fabrics by the sol-gel and linking agent methods were found to be intact after various cycles of domestic washing. Knitted fabrics containing ZnO nanoparticles showed moderate to high ultraviolet protection factor (UPF) values, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 21 publications
0
44
0
Order By: Relevance
“…TiO 2 9 2 fabric after washing can be also found in literature and it is assigned to morphological change of textile nano-composite that occurred after washing (Paul et al 2010). Daoud and co-workers suggested that the good laundering durability of Co fabrics loaded with TiO 2 NPs can be attributed to the formation of covalent bonding resulting from a dehydratation reaction between the hydroxyl groups of cotton and the hydroxyl groups of TiO 2 Xin et al 2004).…”
Section: R%mentioning
confidence: 83%
“…TiO 2 9 2 fabric after washing can be also found in literature and it is assigned to morphological change of textile nano-composite that occurred after washing (Paul et al 2010). Daoud and co-workers suggested that the good laundering durability of Co fabrics loaded with TiO 2 NPs can be attributed to the formation of covalent bonding resulting from a dehydratation reaction between the hydroxyl groups of cotton and the hydroxyl groups of TiO 2 Xin et al 2004).…”
Section: R%mentioning
confidence: 83%
“…Consumers are demanding textile products with enhanced functionalities, such as antibacterial [31][32][33][34], antistatic [35][36][37], stain resistant [38,39], and UV protection [40][41][42]. Wool fiber is a superior natural textile material due to its resilience and comfort attributes.…”
Section: Introductionmentioning
confidence: 99%
“…These radiations are present in natural terrestrial sunlight in different amounts due to the filtering activity of the upper atmosphere and local conditions (latitude, altitude and clouds). UV-C and most of UV-B are filtered by the ozone layer (Ghule et al 2006;Paul et al 2010). Here, UV spectra were recorded for untreated and treated cotton fibers by measuring the transmission.…”
Section: Uv-blocking Propertymentioning
confidence: 99%
“…It can efficiently absorb UV radiation coming from the atmospheric ozone layer (Sato and Ikeya 2004) and can be directly used in daily applications. Recently, many studies have been devoted to improve the UV protection function of cotton fabrics using nano-ZnO (Yadav et al 2006;Kathirvelu et al 2009;Mao et al 2009;Zohdy et al 2009;Farouk et al 2010;Paul et al 2010;Wang et al 2011). Yadav et al (2006 applied ZnO nanoparticles onto cotton fabrics using acrylic binder.…”
Section: Introductionmentioning
confidence: 99%